Assessment of Hearing Loss in Minor Head Injury: A Prospective Study - Bansal, Sumit; Preetam, Chappity; Patnaik, Ashis; Sahu, Rabi Narayan (Asian Journal of Neurosurgery, 2022)
Introduction Hearing loss following a head injury is common and well known. The numbers of road traffic accidents have increased recently, with minor head injuries being very common, and usually go unreported. Hearing loss after a minor head injury is often unnoticed. Available literature is limited in this regard.Objective This study was done to assess hearing loss in patients with minor head injuries and to define its natural history and progression/regression by a serial assessment of hearing.Methods This prospective study was done in the Department of Neurosurgery, AIIMS, Bhubaneshwar, Odisha, India, for a period of 24 months to look at the profile of hearing levels of patients presenting with history suggestive of minor head injury.Results This study has shown that some form of hearing loss is common after a minor head injury and should be evaluated in all patients to detect subclinical hearing loss. A significant number of patients having minimal or a mild degree of hearing loss, if managed properly, improve to preinjury status. Distortion product oto-acoustic emission testing should be used as the screening and follow-up tool.Conclusion This study highlights the importance of hearing assessment in minor-head-injury patients and the prognosis of recovery as per the severity of hearing loss and head injury.
Keywords: road traffic accidents; hearing loss; minor head injury; outcome; hearing assessment